Product innovation in UK manufacturing companies - Goffin, Keith; Szwejczewski, Marek; Sweeney, Michael; New, Colin (Inderscience, 2000)
In many sectors of the manufacturing industry, product innovation is an important way for companies to achieve competitive advantage. Regular introductions of new products can be essential, especially in fast-moving markets. But how often do companies introduce new products? A database of UK manufacturing plants was analysed to determine the innovation rates and typical product development times in specific industry sectors. The results show a wide spread in the development times and innovation rates even within closely defined sectors - implying that some companies are particularly efficient at product innovation whereas others need to improve. In addition, the research identifies a number of key areas of innovation, which require further investigation, both within the UK and on an international basis.
Keywords: cycle times; new product development; product innovation; UK manufacturing